Accuracy and Reliability of the i-STAT Point-of-Care Device for the Determination of Haemoglobin Concentration before and after Major Blood Loss. Issue 4 (July 2014) - Ng, W. L.; Short, T. G.; Gunn, K. N.; Fuge, G. S.; Slon, B.
We investigated the accuracy of i-STAT ® (Abbott Point of Care Inc., Princeton, NJ, USA) haemoglobin (Hb) measurement in surgical patients with an estimated blood loss of ≥25% of total blood volume. Blood tests for i-STAT ® Hb, laboratory Hb (Sysmex XE-2100™, Sysmex Corporation, Kobe, Japan) and total plasma proteins were obtained at the start of surgery (T=0) and when an estimated 25% total blood volume loss had occurred (T=1). Thirty-one patients were recruited. The coefficient of variation of the paired i-STAT Hb estimates was 2.8% and 2.9% at T=0 and T=1, respectively. The mean difference between i-STAT ® and laboratory Hb was −7.6 g/l (standard deviation 6.5) at T=0 and −5.1 g/l (standard deviation 12) at T=1. The mean total plasma protein difference (total plasma protein T=0 minus T=1) was 13.6 g/l (95% confidence interval 10.2 to 17.0). There was poor correlation between total plasma protein and bias in i-STAT ® measurements. The i-STAT ® Hb had an acceptable coefficient of variation, but the Hb levels were lower than those estimated by the laboratory. The standard deviation of i-STAT ® Hb was greater after ≥25% estimated total blood volume loss. Clinicians should not use the i-STAT ® Hb in isolation for clinical decision-making when considering blood transfusion in a situation of 25% or greater blood loss.